Effect of plasticizer and fermetation time on cellulose membrane production and analysis of material property - . FARIDAH; ALFIAN PUTRA; . ELWINA; M. SAMI; NUR AZIZAH (Syiah Kuala University, 2014)
This research has been carried out in cellulose membrane production from bacterial cellulose. Bacterial cellulose is produced from the fermentation process. The purpose of this study was to analysis the effect of cmc, glycerol and fermentation time towards cellulose membrane characteristics. Cellulose membrane made of a combination of coconut water and palm sugar juice as medium fermentation by using Acetobacter xylinum at 2, 4 and 6 days for fermentation time. Cellulose membrane obtained from a mixture of bacterial cellulose, cmc and glycerol. The addition of cmc and glycerol to improve cellulose membrane characteristics and performance. Based on the analysis results obtained the best performance at 4 days of fermentation time with a concentration of 1.5% cmc and 1.5% glycerol. The thickness of the cellulose membrane was almost the same for all samples and does not affect significantly towards the fermentation time for cellulose membrane production. Cellulose membrane has an asymmetric shape based on morphological analysis using SEM. Besides cellulose membrane has a similar pattern to the weight reduction and has the addition of heat resistance of the membrane. While the results of the IR spectra of cellulose membrane to detect the presence of OH groups, CO, C=C and CH groups that are characteristic of the polymer